PENGARUH KEPERCAYAAN DIRI DAN KEJENUHAN KERJA TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI SEKECAMATAN TANJUNG MEDAN KABUPATEN ROKAN HILIR - Kuswanto, Tri Hadi; Suarman, Suarman; Azhar, Fadly (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2022)
This study aims to determine the effect of variables (1) self-confidence on teacher performance, (2) job saturation on teacher performance, (3) self-confidence and work saturation together on teacher performance. The research respondents were State Elementary School teachers in Tanjung Medan District, Rokan Hilir Regency, totaling 233 people with a sample of 147. The data was collected through questionnaires as a research instrument. The data analysis used is descriptive analysis and inferential statistical analysis. The instrument reliability coefficient was calculated using the Cronbach alpha formula. The results showed that there was a positive and significant effect of self-confidence on teacher performance of 0.159, there was a positive and significant effect of job saturation on teacher performance of 0.112. Meanwhile, together there is an influence of self-confidence and work saturation on teacher performance of 0.264.